Sound Apperception Test: Development and Validation (Global Journal of Human-Social Science, 2015)
We report the development of Sound Apperception Test SAT measuring personality using an alternative auditory form of projective testing Sound effects designed to measure four personality dimensions viz intellectual functioning interpersonal adjustment task orientation and emotional embedded-ness were created Stimulus analysis was carried out on a randomly drawn sample n 440 Twenty-four out of the 60 sound effects had more than 75 consensus among expert raters and were retained Six of the 18 sound effects were common for males and females and six each were gender-specific The test-retest reliability for males n 107 was 0 692 0 765 p 0 01 and for females n 69 it was 0 644 0 841 p 0 01 The validity for males n 178 was 0 652 0 691 p 0 01 and for females n 64 it was 0 675 0 71 p 0 01
Keywords: sound apperception test; tat; sound effect; sat